2020
DOI: 10.1057/s41267-020-00356-4
|View full text |Cite
|
Sign up to set email alerts
|

Best of both worlds: How embeddedness fit in the host unit and the headquarters improve repatriate knowledge transfer

Abstract: Knowledge transfer within multinational enterprises is a source of competitive advantage. However, we know little about repatriates' role in reverse knowledge transfer upon their return to headquarters (HQ). Using an organizational embeddedness perspective, we conceptualized how embeddedness fit -individuals' perceived match between their knowledge and skills and the job requirements -during the expatriation assignment and upon repatriation predicts repatriate knowledge transfer. To test the hypotheses, we col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 92 publications
0
47
0
5
Order By: Relevance
“…First, this study offers a theoretical justification for the role of group dynamics as a factor that can promote or stymy knowledge sharing in global contexts, which has so far remained largely unexamined. Currently, the factors that are thought to promote knowledge sharing in global contexts include (1) individual-level factors, such as cultural intelligence (Vlajcic et al, 2019a), organizational embeddedness (Froese et al, 2021); (2) dyadic factors, such as abilities, motivations and opportunities to share (Burmeister et al, 2018;Amir et al, 2020;Shao and Ariss, 2020), the relationship between local and international employees (Bonache and Zarraga-Oberty, 2008), the role of empowering leadership for the leader-follower relationship (Bucher et al, 2020); (3) organizational-level factors, such as organizational support (Froese et al, 2021;Lazarova and Tarique, 2005), high-commitment human resource practices (Shao and Ariss, 2020), geographical distance between headquarters and subsidiaries (Vlajcic et al, 2019b), subsidiary absorptive capacity (Chang et al, 2012) and (4) the characteristics of the knowledge being shared (Duvivier et al, 2019;Bonache and Zarraga-Oberty, 2008). This current research expands the set of potential factors that promote knowledge sharing in global contexts to include group dynamics arising from international experience-based cognitive, relational and structural capital of the group.…”
Section: Implications For Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…First, this study offers a theoretical justification for the role of group dynamics as a factor that can promote or stymy knowledge sharing in global contexts, which has so far remained largely unexamined. Currently, the factors that are thought to promote knowledge sharing in global contexts include (1) individual-level factors, such as cultural intelligence (Vlajcic et al, 2019a), organizational embeddedness (Froese et al, 2021); (2) dyadic factors, such as abilities, motivations and opportunities to share (Burmeister et al, 2018;Amir et al, 2020;Shao and Ariss, 2020), the relationship between local and international employees (Bonache and Zarraga-Oberty, 2008), the role of empowering leadership for the leader-follower relationship (Bucher et al, 2020); (3) organizational-level factors, such as organizational support (Froese et al, 2021;Lazarova and Tarique, 2005), high-commitment human resource practices (Shao and Ariss, 2020), geographical distance between headquarters and subsidiaries (Vlajcic et al, 2019b), subsidiary absorptive capacity (Chang et al, 2012) and (4) the characteristics of the knowledge being shared (Duvivier et al, 2019;Bonache and Zarraga-Oberty, 2008). This current research expands the set of potential factors that promote knowledge sharing in global contexts to include group dynamics arising from international experience-based cognitive, relational and structural capital of the group.…”
Section: Implications For Theorymentioning
confidence: 99%
“…First, this study offers a theoretical justification for the role of group dynamics as a factor that can promote or stymy knowledge sharing in global contexts, which has so far remained largely unexamined. Currently, the factors that are thought to promote knowledge sharing in global contexts include (1) individual-level factors, such as cultural intelligence (Vlaj ci c et al, 2019a), organizational embeddedness (Froese et al, 2021); (2) dyadic factors, such as abilities, motivations and opportunities to share (Burmeister et al, 2018;Amir et al, 2020;Shao and Ariss, 2020), the relationship between local and international employees (Bonache and Zarraga-Oberty, 2008), the role of empowering leadership for the leader-follower relationship (Bucher et al, 2020);…”
Section: Implications For Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Future research could extend the analysis on expatriate and HCN immediate and long-term success. For instance, considering the importance of knowledge and innovation, future research could explore the immediate effects on knowledge sharing when expatriates and HCNs work together and long-term effects after expatriates return to headquarters (Froese et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The conducted research is based on the theoretical basis created by both foreign and Russian scientists. Of particular value were scientific works in which: conceptual approaches to the origins of the effects of trade relations are outlined (Viner, 1950); theoretical foundations of economic integration are revealed (Krugman and Venables, 1996;Lumineau et al, 2021;Tan et al, 2020), the dynamics, stages, and forms of economic integration associations (Balassa, 1967;Glazyev, 2019; Postel-Vinay, 2020); the forecast of the strength of economic integration in the terms of global challenges is given (Chia and Plummer, 2015;Shenkar et al, 2020); the applied aspects of the analysis of integration processes are revealed (Akhunbayev et al, 2020;Froese et al, 2021;Kets and Sandroni, 2021;Kӧpid, 2015); the vision of possible solutions to integration problems (Jones, 2015;Krugman and Venables, 1996;Oliveira and Lumineau, 2019). The statistical data and analytical reports of the Eurasian Development Bank, international reports of researchers representing the EU and EAEU member states, as well as other materials of other authoritative organizations served as an information base.…”
Section: Methodsmentioning
confidence: 99%